Influence of CO2‐wettability on CO2 migration and trapping capacity in deep saline aquifers. Issue 2 (18th November 2016) - Al‐Khdheeawi, Emad A.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Iglauer, Stefan
Abstract: CO2 migration and trapping capacity in deep saline aquifers are highly influenced by various rock and fluid parameters. One of the key parameters, which has received little attention, is CO2 ‐wettability. We thus simulated the behavior of a CO2 plume in a deep saline aquifer as a function of rock wettability and predicted various associated CO2 migration patterns and trapping capacities. We clearly show that CO2 ‐wet reservoirs are most permeable for CO2 ; CO2 migrates furthest upwards and the plume has a candle‐like shape, while in a water‐wet reservoir the plume is more compact and rain‐drop shaped. Furthermore, higher residual trapping capacities are achieved in water‐wet rock, while solubility trapping is more efficient in CO2 ‐wet rock. We thus conclude that rock wettability has a highly significant impact on both CO2 migration and trapping capacities and that water‐wet reservoirs are preferable CO2 sinks due to their higher storage capacities and higher containment security. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd.